A desertificação em São João do Cariri (PB): uma análise das vulnerabilidade - Tavares, Válter Cardoso (2014)
This paper addresses the desertification of the municipality of the São João do Cariri/ PB and analyzes the socioeconomic and environmental vulnerabilities, revealing the interplay between the vulnerability of rural households surveyed with the phenomenon of desertification. Desertification is a major problem today and cause deleterious effects to populations. The Brazilian semiarid region is the most affected and geoecologically pre - disposed to this phenomenon region. The East Cariri and specifically the city under study is within the context of desertification. This municipality shows serious signs of degradation, such as desertification nucleus. Deforestation therefore, and inappropriate agricultural practices contribute greatly to the aggravation of the phenomenon. The present work aims to generate the index of vulnerability to desertification in São João do Cariri and simultaneously do an analysis of it. To perform the job evaluation questionnaires of socioeconomic and environmental conditions of farmers in the municipality of the ray tracing with respect to measurement of the vulnerabilities were used. In addition, literature searches were made on the Internet, articles, publications in journals, dissertations, theses and books on the subject at hand. The methodology used in the diagnosis of socioeconomic and environmental vulnerability is adapted by Rocha (1997 ), to Rio Grande do Sul, and Araújo (2002 ), Moraes Neto (2003 ), Alencar (2004 ), Duarte (2008 ) and Silva et al. (2002) for the Semi-Arid Paraiba. The study of vulnerabilities drew on a survey of rural households in the municipality of the ray tracing. The questionnaire was applied to 10 % of rural households in the city under study. For the realization of socio-economic and environmental analysis four factors related to the vulnerabilities and their respective variables were used, namely Factor Social Vulnerability: demographics, housing, food consumption, participation in organizations, and rural health; Economic Vulnerability Factor: agricultural production, animal work, income, etc.; Technological Vulnerability: use of technologies, ownership of machinery, equipment and technical assistance; Vulnerability to Drought: water resources, management of savanna, exploitation of native species, water storage, herd reduction, the occupation droughts, migration, among others.